Prophetic Pedagogy and Moderate Islamic Education: An Analysis of Washatiyah Learning Methods in Ar-Rasūl al-Mu‘allim - Sofiyatun Muniroh; Rodliatul Millah; Farid Qomaruddin; Lukman Khoirin (Attanwir : Jurnal Keislaman dan Pendidikan, 2026)
Balanced and moderate Islamic education is essential for addressing contemporary challenges such as extremism, rigid formalism, and impersonal pedagogical practices. This study examines the moderation-based teaching methods (washatiyah) of Prophet Muhammad ﷺ  documented in Ar-Rasūl al-Mu‘allim, focusing on the integration of cognitive, affective, and psychomotor dimensions. Employing a qualitative library research approach, the study analyzes the Prophet’s pedagogical principles, including tadarruj (gradual learning), dialogical engagement, role modeling, contextual demonstration, and taysir (ease and facilitation). The findings indicate that these methods effectively balance intellectual rigor, ethical cultivation, and practical application, fostering learners who are morally responsible, spiritually grounded, and socially inclusive. Furthermore, the moderation-based pedagogy remains highly relevant for contemporary Islamic education, providing educators with strategies to cultivate critical thinking, ethical reasoning, and holistic character formation in diverse learning contexts.